Effect of intravenous dexmedetomidine administered as bolus or as bolus-plus-infusion on subarachnoid anesthesia with hyperbaric bupivacaine - Upadhya R Kavya; Shenoy Laxmi; Venkateswaran Ramkumar (Wolters Kluwer Medknow Publications, 2018)
Background: Subarachnoid anesthesia is a widely practiced regional anesthetic for infraumbilical surgeries. Intravenous dexmedetomidine is known to prolong both sensory and motor blockade when administered along with subarachnoid anesthesia. Material and Methods: Seventy-five patients scheduled to undergo elective infraumbilical surgeries under subarachnoid anesthesia were randomly allocated to one of the three groups. Group B received intravenous saline over 10 min followed by 12.5 mg intrathecal bupivacaine and then intravenous saline over 60 min. Group bupivacaine + dexmedetomidine bolus (BDexB) received intravenous dexmedetomidine (1 μg/kg) over 10 min followed by 12.5 mg intrathecal bupivacaine and then intravenous saline over 60 min. Group bupivacaine + dexmedetomidine bolus-plus-infusion (BDexBI) received intravenous dexmedetomidine (0.5 μg/kg) over 10 min followed by 12.5 mg intrathecal bupivacaine and then intravenous dexmedetomidine (0.5 μg/kg) over 60 min. Onset of analgesia (at T10), complete motor block (Bromage score 3), and highest level of analgesia were noted. Sensory and motor levels were checked periodically till sensory recovery (at S2-S4) and complete motor recovery (Bromage score 0). Ramsay sedation score and incidence of bradycardia/hypotension were noted. Results: Sensory recovery was significantly longer in Group BDexB (303 min) and Group BdexBI (288 min) as compared to Group B (219.6 min). Motor recovery was also significantly prolonged in Group BDexB (321.6 min) and Group BDexBI (302.4 min) as compared to Group B (233.4 min). Patients receiving dexmedetomidine were sedated but were easily arousable. Conclusion: Intravenous dexmedetomidine given as bolus or bolus-plus-infusion with intrathecal hyperbaric bupivacaine prolongs both sensory and motor blockade.